THE INFLUENCE OF THE WORK ENVIRONMENT AND SUPERVISION ON EMPLOYEE MORALE ON COMMUNICATION AND INFORMATION SERVICE CENTRAL TAPANULI REGENCY - Alviansa Pasaribu; Mhd. Shafwan Koto; Anna Basriyani (Patua : Journal of Business Administration and Management, 2025)
This study aims to determine the Influence of Work Environment and Supervision on Employee Morale at the Communication and Information Service of Central Tapanuli Regency. The type of research used is a quantitative research method with a descriptive approach. The sample totaled 41 people. The results of the study were found based on the Determination Coefficient Analysis obtained of 0.611, meaning that the work spirit of 61.1% was determined by the work environment and supervisors together and the remaining 38.9% was determined by other factors that were not discussed in this study. The results of the t-test are known to be 3,511 > ttable 2,024 with a significance of 0.001 < 0.05 and t-count supervision of 2,622 > ttable 2.02439 with a significance of 0.012 < 0.05, so the hypothesis formulated that the work environment has a positive and significant effect on the employee's morale and supervision has a positive and significant effect on the employee's morale can be accepted. Furthermore, from the results of the F test, it is known that the Fcal value is 29,873 > Ftable 3.24 and the significance of Fcal is 0.000 < 0.05 so that the hypothesis formulated by the Work Environment and Supervision has a Positive and Significant Effect on the Employee Morale at the Communication and Information Service of Central Tapanuli Regency can be accepted.